2020
DOI: 10.1177/0194599820931455
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Corticosteroid Therapy: Systematic Review and Meta‐analysis of Reported Safety and Adverse Effects in Adults

Abstract: Objectives To address concerns related to the safety profile of both Food and Drug Administration (FDA)–approved and non–FDA-approved intranasal corticosteroid (INCS) use in the adult population. Data Source Systematic review of MEDLINE, PubMed, and EMBASE databases using a comprehensive search strategy including all INCS formulations and adverse events. The study design was developed using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Additional sources were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 62 publications
2
20
0
Order By: Relevance
“…While the systematic review and meta-analysis from 2020 showed that INCSs in adults are generally safe, 40 concerns have been raised about the potential adverse events of chronic INCS use on growth in children, 41 , 42 despite conflicting evidence for this being available in published studies. For example, use of BDP ANS (168 µg BID) was shown to significantly affect growth rate in children after one year of treatment, 43 and BUD MDI (200 μg BID) was found to significantly reduce lower-leg growth in children after six weeks of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…While the systematic review and meta-analysis from 2020 showed that INCSs in adults are generally safe, 40 concerns have been raised about the potential adverse events of chronic INCS use on growth in children, 41 , 42 despite conflicting evidence for this being available in published studies. For example, use of BDP ANS (168 µg BID) was shown to significantly affect growth rate in children after one year of treatment, 43 and BUD MDI (200 μg BID) was found to significantly reduce lower-leg growth in children after six weeks of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Glucocorticoids are applied not only systemically but also locally as intranasal corticoids spray. Especially the intranasal administration is one of the first choices of conservative treatments of CRS and AR due to its confirmed efficacy and safety (47)(48)(49).…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…19,20 A meta-analysis and systematic review by Donaldson et al of 60 studies concluded that INCS are safe in the adult population. 21 High-volume irrigations. Given the well-documented increase in sinus penetration with high-volume irrigations, particularly in postoperative cases, the off-label use of budesonide irrigations has become increasingly popular in CRS treatment.…”
Section: Delivery Devicesmentioning
confidence: 99%